Structure and Emerging Functions of LRCH Proteins in Leukocyte Biology - Rivière, Thibaud; Bader, Almke; Pogoda, Kristin; Walzog, Barbara; Maier-Begandt, Daniela (Frontiers in Cell and Developmental Biology, 2020)
Actin-dependent leukocyte trafficking and activation are critical for immune surveillance under steady state conditions and during disease states. Proper immune surveillance is of utmost importance in mammalian homeostasis and it ensures the defense against pathogen intruders, but it also guarantees tissue integrity through the continuous removal of dying cells or the elimination of tumor cells. On the cellular level, these processes depend on the precise reorganization of the actin cytoskeleton orchestrating e.g. cell polarization, migration and vesicular dynamics in leukocytes. The fine-tuning of the actin cytoskeleton is achieved by a multiplicity of actin-binding proteins inducing e.g. the organization of the actin cytoskeleton or linking the cytoskeleton to membranes and their receptors. More than a decade ago, the family of leucine-rich repeat (LRR) and calponin homology (CH) domain-containing (LRCH) proteins has been identified as cytoskeletal regulators. The LRR domains are important for protein-protein interactions and the CH domains mediate actin binding. LRR and CH domains are frequently found in many proteins, but strikingly the simultaneous expression of both domains in one protein only occurs in the LRCH protein family. To date, one LRCH protein has been described in drosophila and four LRCH proteins have been identified in the murine and the human system. The function of LRCH proteins is still under investigation. Recently, LRCH proteins have emerged as novel players in leukocyte function. In this review, we summarize our current understanding of LRCH proteins with a special emphasis on their function in leukocyte biology.